(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Distance of a villagefrom a city or town (district or a block) may be a crucial factor for themarketer who is planning to tap the rural market. Because it is assumed thatthe ruralites who live in the periphery of towns or cities have differentbuying attitude and expenditure pattern than those who reside in villages faraway from the cities or towns. Those who live in the neighbour of the city ortowns are assumed to be highly influenced by their urban counterparts becauseof their continuous interaction with urban people and exposure to their lifestyle and also an access to certain services and facilities which are enjoyedby urban people. Whereas on the contrary far away people cannot enjoy thesefacilities so they may have different mindset regarding the purchase of durables.It can be seen from study that 43.3 percent of the respondents reside within the distance of 10 kms. fromblocks/districts while 41 per cent reside in the range of 20 kms. from theirrespective blocks/districts. 15.7 per cent respondents live outside theperiphery of 20 kms. from their districts/blocks. It follows that mostof the respondents in the sample reside within the range of 20 kms. from thenearest block/districts. For a marketer therefore, it represents a segment ofthe market, which he can tap for his advantage in the sense that he can arrangefor the services to be provided at a place, which is relatively closer to theplace of residence of the majority.